First report of gastroliths in the Early Cretaceous basal bird Jeholornis. (April 2018) - O'Connor, Jingmai; Wang, Xiaoli; Sullivan, Corwin; Wang, Yan; Zheng, Xiaoting; Hu, Han; Zhang, Xiaomei; Zhou, Zhonghe
Abstract: Seeds preserved in association with the holotype of Jeholornis prima provided the first direct evidence of granivory in any Mesozoic bird. Although this long boney-tailed bird also displays several morphological indicators correlated with herbivory such as reduced dentition and a deep mandible, Jeholornis has not been previously reported to possess a gastric mill. However, this feature is commonly linked to herbivory in theropod dinosaurs and present in at least one sympatric ornithuromorph and the basal pygostylian Sapeornis, which also preserve direct evidence of granivory. Here we describe gastrolith masses preserved in five specimens of Jeholornis . The cluster of gizzard stones is nearly identical in each specimen, consisting of a tightly associated mass of proportionately small stones. Three previously undescribed specimens preserving seeds are also identified. Unlike in Sapeornis and a previously described ornithuromorph, no specimen of Jeholornis preserves both seeds and gastroliths. This may be due to the fact that, unlike in other Early Cretaceous birds, the seeds preserved in specimens of Jeholornis are found in the abdomen, suggesting that Jeholornis may have resembled extant ratites in lacking an esophageal crop. Consistent differences in the preservation and morphology of the gastrolith mass between Jeholornis and other early birds hint at subtle variations in alimentary function among basal lineages. Differences in ingested seed morphology among taxa in turn suggest these functional variations may be at least partially related to differences in diet.